(untitled) (Jurnal Ilmu Komunikasi dan Bisnis, 2021)
Internet as a new media marks a new period of interactive technology and network communication, especially cyberspace will change society (Littlejohn &Foss, 2014). The Internet makes it easy for its users to access information. With the online system, information can be accessed whenever and wherever the user is located. One form of new media is social media, such as Twitter, Facebook, and Instagram. Instagram can be an alternative medium in finding the information that users need because there are accounts that share information about certain things, such as @infobdg, @infojkt and also @suarasurabayamedia. This research aims to find out how effective Instagram accounts @suarasurabayamedia in fulfilling information needs for followers from Surabaya. The theory of information needs used in this study is the theory put forward by Guha. The method used in this study is descriptive quantitative with data sources from questionnaires and literature that correspond to the problems studied. The results of the study obtained is the average score on the current need approach dimension is 3,150, everyday need approach dimension is 3,035, exhaustic need approach dimension is 3,003, and the average score for the catching-up need approach dimension is 3,110. The results of these four dimensions is effective.